2021
DOI: 10.1186/s12883-021-02218-4
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab and risk of COVID-19 infection and its severity in patients with MS and NMOSD

Abstract: Background Choosing a safe disease modifying therapy during the COVID-19 pandemic is challenging. This case series study was conducted to determine the incidence rate and the course of Covid-19 infection in MS/NMOSD patients treated with Rituximab. Methods In this study, we designed a web-based questionnaire. Baseline information such as patient- reported walking disability, total number of Rituximab infusions received, delayed injections, occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…Nevertheless, differently from findings reported by Esmaeili et al. ( 24 ), rituximab administration was not associated with higher risk of severe side effects and more severe WHO clinical progression scale. It is however reported a prolonged SARS-CoV-2 infection in patient und rituximab regimen ( 25 ).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, differently from findings reported by Esmaeili et al. ( 24 ), rituximab administration was not associated with higher risk of severe side effects and more severe WHO clinical progression scale. It is however reported a prolonged SARS-CoV-2 infection in patient und rituximab regimen ( 25 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Nevertheless, it is reported that the immunocompromised individuals are more likely to produce variants due to long-term virus replication, which is probably due to the selective pressure from therapeutic such antibody cocktails ( 23 ). We cannot exclude that the prolonged positivity on NFS have been amplified by concomitant rituximab therapy ( 24 , 25 ). Nevertheless, differently from findings reported by Esmaeili et al.…”
Section: Discussionmentioning
confidence: 99%
“…Anti CD20 monoclonal antibodies (rituximab and ocrelizumab) are considered to be associated with severe forms of COVID-19 ( Cabreira et al, 2021 ; Esmaeili et al, 2021 ; Safavi et al, 2020 ). Although, some contradicting results are reported ( Sharifian-Dorche et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A case series from Spain reported mild COVID-19 infections with only one hospitalization in patients taking anti-CD20 with multiple sclerosis, however, SARS-CoV2 was diagnosed only by symptoms [ 29 ]. In contrast, a case series in Tehran evaluated COVID-19 in nine patients with multiple sclerosis taking rituximab with five requiring hospitalization, two of which required ICU admission and two died, giving a mortality of 40% for those admitted [ 30 ]. None of the patients reported steroid use prior to their COVID-19 diagnosis [ 30 ].…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)mentioning
confidence: 99%
“…In contrast, a case series in Tehran evaluated COVID-19 in nine patients with multiple sclerosis taking rituximab with five requiring hospitalization, two of which required ICU admission and two died, giving a mortality of 40% for those admitted [ 30 ]. None of the patients reported steroid use prior to their COVID-19 diagnosis [ 30 ]. A case series in Spain evaluated 13 patients with probable or confirmed COVID-19 treated with rituximab in the 12 months before the study [ 31 ].…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)mentioning
confidence: 99%